Bioactive peptides from venoms against glioma progression - Majc, Bernarda; Novak, Metka; Lah, Tamara T.; Križaj, Igor (Frontiers in Oncology, 2022)
Venoms are complex mixtures of different molecules and ions. Among them, bioactive peptides have been found to affect cancer hallmarks, such as cell proliferation, cell invasion, cell migration, and can also modulate the immune response of normal and cancer-bearing organisms. In this article, we review the mechanisms of action on these cancer cell features, focusing on bioactive peptides being developed as potential therapeutics for one of the most aggressive and deadly brain tumors, glioblastoma (GB). Novel therapeutic approaches applying bioactive peptides may contribute to multiple targeting of GB and particularly of GB stem cells. Bioactive peptides selectively target cancer cells without harming normal cells. Various molecular targets related to the effects of bioactive peptides on GB have been proposed, including ion channels, integrins, membrane phospholipids and even immunomodulatory treatment of GB. In addition to therapy, some bioactive peptides, such as disintegrins, can also be used for diagnostics or are used as labels for cytotoxic drugs to specifically target cancer cells. Given the limitations described in the last section, successful application in cancer therapy is rather low, as only 3.4% of such peptides have been included in clinical trials and have passed successfully phases I to III. Combined approaches of added bioactive peptides to standard cancer therapies need to be explored using advanced GB in vitro models such as organoids. On the other hand, new methods are also being developed to improve translation from research to practice and provide new hope for GB patients and their families.